International and Cultural Psychology Series 2007
DOI: 10.1007/978-0-387-70990-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Assessment of Psychological Trauma and PTSD

Abstract: A Continuation Order Plan is available for this series. A continuation order will bring delivery of each new volume immediately upon publication. Volumes are billed only upon actual shipment. For further information please contact the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(9 citation statements)
references
References 529 publications
(517 reference statements)
1
8
0
Order By: Relevance
“…The possible role of social complexity beliefs as a factor that might influence PTG may help explain why some individuals are more open to considering the positive side of the trauma experience and later to resolving and accepting this experience. These points are consistent with general suggestions that researchers, practitioners, and policymakers consider the broader cultural context when designing and implementing interventions or policies for trauma survivors (Marsella, 2010; Wilson & Tang, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…The possible role of social complexity beliefs as a factor that might influence PTG may help explain why some individuals are more open to considering the positive side of the trauma experience and later to resolving and accepting this experience. These points are consistent with general suggestions that researchers, practitioners, and policymakers consider the broader cultural context when designing and implementing interventions or policies for trauma survivors (Marsella, 2010; Wilson & Tang, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…The IES-R 7 has 22 items and ranges 0-4, with scores ≥1.6 indicating substantial PTSD symptoms. 2 For this study, HADS data were available at 6-month follow-up from all 5 studies, and at 12-month follow-up from ALTOS, ICAP, and PRaCTICaL.…”
Section: Methodsmentioning
confidence: 99%
“…14 A recent study of ARF survivors reported that >38% screened positive for general anxiety, >26% for depression, >22% for post-traumatic stress disorder (PTSD) during 2-year longitudinal follow-up. 5 The Hospital Anxiety and Depression Scale (HADS) 6 and Impact of Event Scale-Revised (IES-R) 7 have been used in studies of ICU survivors 3,5,810 to assess symptoms of these conditions. While the HADS and IES-R demonstrate good reliability and validity in ICU survivors 2,11 and other populations 1214 , the minimal important difference (MID) has not been reported in ARF survivors.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study (n=1194) using convenience sampling found 47.3% anxiety (using a lower cut-off than us of ≥8 on the GAD-7), 46.9% depression (using the same cut-off as us of ≥10), and 22.5% PTSD (using a different measure: ITQ, [23]). [24] A different cross-sectional study (n=2773) found levels (using the same cut-off scores of ≥10 for the GAD-7 and PHQ9, though a different PTSD measure; IES-R, [25]), of 33.1% for probable anxiety, 28.1% for probable depression, and 14.6% for PTSD symptoms. [26] Elevated prevalence of anxiety and depression compared to our study may be attributable to differing sample demographic factors, particularly sex, which was over-represented in these studies.…”
Section: Uk Hcwsmentioning
confidence: 98%